Pengaruh Aksesibilitas Lokasi Dan Suku Bunga Kredit Terhadap Minat Beli Pada Perumahan Wira Asri Rantauprapat - Raja Saul Marto Hendry (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2021)
: This study entitled The effect of location accessibility and lending rates on buying interest in Wira Asri Rantauprapat housing. This research is a survey research with quantitative approach. The sample was 34 employees. The data collection techniques used were questionnaires, Likert measurement scale and documentation.With data processing techniques validity test, reliability test, correlation, multiple linear regression analysis, and the coefficient of determination by using SPSS 23.0 for windows.Based on the T test for the location can be concluded that for thitung of 2.412 while T table 1.6 (t count greater than ttable)which means that the time of work significantly affect the performance of employees and based on the F test for work facilities thitung of 2.338 while T table 1.703 (t count greater than ttable)which means work facilities significantly affect the performance of employees. Based on the test results F(simultaneous) variable execution time of work and work facilities simultaneously have a significant effect on employee performance, it can be seen from the F count = 14.254 and F Table = 3.12 in this case F count is greater than F table and significant value is 0.002 smaller than the value of alpha 0.05. Based on the Adjusted R square value of 0.270 or 27.0% shows that simultaneously the time of work and work facilities contribute to Employee Performance by 27.0%, while the remaining 72% is explained by other variables that are not proposed in this study.